Peningkatan Keterampilan Berpikir Kritis di Perguruan Tinggi Melalui Metode Diskusi - Muhammad, Ibrahim; Adam, Adiyana (Peneliti.net, 2024)
The purpose of this study is to increase the effectiveness of learning in higher education (study case; discussion as a means of boosting the number of students who engage in critical reflection at Institut Agama Islam Negeri Ternate). The ability to discuss as a means of improving students' critical thinking skills while fostering a sense of readiness to anticipate global changes. This study employs a kualitatif desk research approach using literature review, participant observation, and student interviews at Institut Agama Islam Negeri Ternate. The results of this study indicate that the discussion method for teaching is one of the most enjoyable approaches. Because of this, under the Abstracles learning paradigm, the teacher must be proficient in developing discussion techniques in order to convey the students' abilities, solicit critical feedback, quantify their progress in the discussion, and assess the students' own learning outcomes. Based on the actual research findings, it was discussed that students greatly require appropriate critical analysis in order to improve their professional competence and mastery of the subject.